The Median Voter Takes it All: Preferences for Redistribution and Income Inequality in the EU-28 - Marco Colagrossi; Stelios Karagiannis; Roman Raab (Publications Office of the European Union, 2019)
The relation between income inequality and support for redistributive policies has long being debated by social scientists, albeit with mostly contrasting findings. We shed light on this puzzle by exploiting a novel EU-28 wide survey (Eurobarometer 471) and matching it with an array of regional and national inequality measures. Using binary choice models, we show that support for redistribution is positively linked with the level of income inequality. The same association is found for perceptions of inequality being too high. In addition, we exploit alternative proxies of socio-economic status as well as subjective beliefs about fairness in the society. We document that individuals believing to be at the top of the social ladder, as well as people considering equal opportunities to be in place, are less supportive of gov- ernment intervention to reduce inequalities. Our results are robust to different measures of inequalities, additional controls as well as a cross-validation with a widely recognized survey (ESS). We conclude that for the planning of policies based on social preferences, inequality matters.
Keywords: D31; D63; H53; 330; Income inequality; preferences for redistribution; perceptions of inequality